Bridging the Gap: Using the Brief Student–Teacher Classroom Interaction Observation to Inform Classroom Practices. (December 2016) - Reinke, Wendy M.; Herman, Keith C.
The brief Student–Teacher Classroom Interaction Observation (ST-CIO) is a direct observation assessment that evaluates interactions between teachers and students. The measure was developed for use in classrooms during academic instruction to determine the frequency of teacher use of reprimands and praise toward a student, as well as the frequency of a student disruptive behavior. This article summarizes the purpose, procedures, and evidence base currently available in the literature to support the ST-CIO and offers ideas for how this observation system can be used to improve classroom practices.